Neonatal Extremity Compartment Syndrome: A Rare Diagnosis Requiring Prompt Recognition - Nicholas T. Severyn; Kok Lim Kua (Thieme Medical Publishers, Inc., 2020)
Neonatal extremity compartment syndrome is an extremely rare diagnosis. Risk factors that predispose infants to a hypercoagulable state or trauma have been implicated, but the exact mechanisms remain poorly understood. The hallmark of the condition is extremity swelling with sentinel skin changes. We report a case of upper extremity compartment syndrome from initial presentation until 3 months after discharge and discuss the importance of prompt diagnosis and timely surgical evaluation.